The audience's perception towards RTM's TV programs and its corporate image in Selangor / Nursyamimi Mohd Anuar - Mohd Anuar, Nursyamimi (Faculty of Business and Management, 2006)
The purpose of this research is to study the audience's perception towards RTM's TV programs and its Corporate Image In Selangor. Moreover, this study is to identify the attributes that influence the sensitivity of audience towards the value of TV programs offered by RTM and to find out the attributes of RTM's corporate image which affects the perception of the audience. It is a believed that the programs offered will determine whether the audience have a good or poor perception towards RTM's image.